2022
DOI: 10.1155/2022/7527457
|View full text |Cite
|
Sign up to set email alerts
|

A Framework of the Training Module for Untrained Observers in Usability Evaluation Motivated by COVID-19: Enhancing the Validity of Usability Evaluation for Children’s Educational Games

Abstract: The usability evaluation of educational games is an important task, especially for children. By applying Jakob Nielsen’s ten heuristics, most of the HCI designs can be evaluated, but when educational games are involved, where the user being observed is a child between the ages of six and eight, many questions arise. Is the observer trained well enough to observe the child’s reactions to the game with regard to its memorability, learnability, ease of use, and enjoyment? Will it be necessary for the observer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…A framework for training the observer (see Figure 2) was proposed by [23]. e training as stipulated by the framework was a requirement to the methodology usage.…”
Section: Usability Evaluation For Children's Mobile Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…A framework for training the observer (see Figure 2) was proposed by [23]. e training as stipulated by the framework was a requirement to the methodology usage.…”
Section: Usability Evaluation For Children's Mobile Learningmentioning
confidence: 99%
“…e findings and recommendations of [23,37] were adapted in this study in performing the actual evaluation, with the purpose of measuring and understanding the present situation in Oman, particularly with respect to the application of imported educational games that has appropriately served the study's purpose.…”
Section: Usability Evaluation For Children's Mobile Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…An important factor in software development is usability because usability can evaluate software features [33]- [35]. There are two types of usability evaluation concepts: summative (related to effectiveness, efficiency, and satisfaction) and formative (related to usability problem detection and intervention design) [36]- [38].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, while conducting a review of the remote usability testing literature for the broader project, we discovered studies that reported on “how to” support the moderator and observer roles [ 7 , 10 , 11 ]. Other authors [ 5 , 6 ] made a call to action to better comprehend complex linkages among human factors (eg, social context or environment or “who” is present at testing), human-computer interaction, and web-based technology and tools to advance the remote usability testing approach.…”
Section: Introductionmentioning
confidence: 99%